Resin composition, resin-coated copper foil, dielectric layer, copper-clad laminate, capacitor element, and capacitor-embedded printed wiring board
The resin composition, comprising epoxy resins, diamine compounds, polyimide resins, and a composite metal oxide filler, addresses the challenge of maintaining capacitance stability and reducing noise in printed wiring boards at high temperatures, achieving excellent dielectric properties and circuit adhesion.
Patent Information
- Application Number
- JP2021202352
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-02-01
- Filing Date
- 2021-12-14
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2039-01-18
AI Technical Summary
Printed wiring boards in portable electronic devices face challenges in reducing noise and maintaining capacitance stability at high temperatures, especially when capacitors are integrated into the inner layers of these boards.
A resin composition comprising epoxy resins, diamine compounds, polyimide resins, and a dielectric filler, specifically a composite metal oxide, is used as a dielectric layer in capacitors. This composition is formulated to suppress capacitance or dielectric constant at high temperatures while ensuring excellent dielectric properties and circuit adhesion.
The resin composition effectively maintains high capacitance and excellent circuit adhesion, even at elevated temperatures, thereby enhancing the performance and reliability of capacitors in printed wiring boards.
Smart Images

Figure 0007656530000004 
Figure 0007656530000001 
Figure 0007656530000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a resin-coated copper foil, a dielectric layer, a copper-clad laminate, a capacitor element, and a printed wiring board with a built-in capacitor. [Background technology]
[0002] Resin compositions for printed wiring boards with built-in capacitors are known as resin compositions used in the manufacture of copper-clad laminates and printed wiring boards. Such resin compositions function as a dielectric layer in a capacitor when cured. For example, Patent Document 1 (JP Patent No. 4148501) describes a resin composition for printed wiring boards with built-in capacitors, which contains 20 to 80 parts by weight of an epoxy resin and 20 to 80 parts by weight of an aromatic polyamide resin (based on 100 parts by weight of the resin component), and contains 75 to 85 wt% of a dielectric filler (based on 100 wt% of the resin composition). Patent Document 2 (WO 2009 / 008471) describes a resin composition for manufacturing printed wiring boards with built-in capacitors, which contains 25 to 60 parts by weight of an epoxy resin, 28 to 60 parts by weight of an active ester resin, and 1 to 20 parts by weight of a polyvinyl acetal resin (based on 100 parts by weight of the resin component), and contains 65 to 85 wt% of a dielectric filler (based on 100 wt% of the resin composition).
[0003] In addition, Patent Document 3 (JP 2007-231125 A) discloses a thermosetting resin composition suitable for manufacturing flexible printed wiring boards and the like that require low dielectric constant and low dielectric loss tangent in the GHz band, which contains a polyimide resin component, an epoxy resin component, an epoxy curing agent component, and a filler component, and describes that silica is preferable as the filler. Meanwhile, Patent Document 4 (JP 2010-539285 A) discloses a composite material for use in capacitors and the like, which contains a mixture of a polymer component that includes an epoxy-containing polymer and the like, and ferroelectric ceramic particles, and describes the use of barium titanate and the like as the ferroelectric ceramic particles. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 4148501 [Patent Document 2] International Publication No. 2009 / 008471 [Patent Document 3] JP 2007-231125 A [Patent Document 4] JP 2010-539285 A Summary of the Invention
[0005] Meanwhile, printed wiring boards are widely used in electronic communication devices such as portable electronic devices. In particular, with the recent trend toward lighter, thinner, shorter, smaller, and more highly functional portable electronic communication devices, reducing noise in printed wiring boards has become an issue. Capacitors are important for noise reduction, and in order to achieve high performance, it is desirable for such capacitors to be small and thin enough to be incorporated into the inner layers of printed wiring boards. Accordingly, capacitance stability is desired to maintain a desired capacitance even under harsh environments such as high temperatures.
[0006] Therefore, in order to improve the performance of electronic communication devices such as portable electronic devices, it is desirable to suppress the decrease in capacitance or dielectric constant of capacitors embedded in printed wiring boards at high temperatures. To achieve this, further improvements in the resin layer that constitutes the dielectric layer of the capacitor are required. At the same time, high adhesion between the resin layer and the circuit (i.e., circuit adhesion) is also desired.
[0007] The present inventors have now discovered that by using a resin composition containing an epoxy resin, a diamine compound and a polyimide resin in a specified mixing ratio together with a specified dielectric filler as the dielectric layer of a capacitor, it is possible to suppress a decrease in capacitance or a decrease in dielectric constant at high temperatures while ensuring excellent dielectric properties and circuit adhesion.
[0008] Therefore, an object of the present invention is to provide a resin composition which, when used as a dielectric layer of a capacitor, can suppress a decrease in capacitance or a decrease in dielectric constant at high temperatures while ensuring excellent dielectric properties and circuit adhesion.
[0009] According to one aspect of the present invention, there is provided a resin composition comprising: A resin component including an epoxy resin, a diamine compound, and a polyimide resin; A dielectric filler which is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta and Bi, in an amount of 60 parts by weight or more and 85 parts by weight or less relative to 100 parts by weight of the solid content of the resin composition; A resin composition is provided comprising:
[0010] According to another aspect of the present invention, there is provided a resin-coated copper foil comprising a copper foil and the resin composition provided on at least one surface of the copper foil.
[0011] According to another aspect of the present invention, there is provided a dielectric layer which is a layer obtained by curing the resin composition.
[0012] According to another aspect of the present invention, there is provided a copper-clad laminate comprising, in order, a first copper foil, the dielectric layer, and a second copper foil.
[0013] According to another aspect of the present invention, there is provided a capacitor element having the above-described dielectric layer.
[0014] According to another aspect of the present invention, there is provided a printed wiring board with an embedded capacitor, comprising the above-described dielectric layer.
[0015] According to another aspect of the present invention, there is provided a method for producing a resin-coated copper foil, the method comprising: applying a resin composition containing a resin component including an epoxy resin, a diamine compound, and a polyimide resin, and a dielectric filler which is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta, and Bi in an amount of 60 parts by weight or more and 85 parts by weight or less based on 100 parts by weight of the solid content of the resin composition, to a copper foil, and drying the resin composition. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a diagram showing the steps of producing the resin-coated copper foil, the copper-clad laminate, and the evaluation circuit in Examples 1 to 25. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] resin composition The resin composition of the present invention includes a resin component and a dielectric filler. The resin component includes an epoxy resin, a diamine compound, and a polyimide resin. On the other hand, the dielectric filler is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta, and Bi. The blending ratio of the dielectric filler is 60 parts by weight or more and 85 parts by weight or less with respect to 100 parts by weight of the solid content of the resin composition. In this way, by using a resin composition containing an epoxy resin, a diamine compound, a polyimide resin, and a dielectric filler in a predetermined blending ratio together with a predetermined dielectric filler as a dielectric layer of a capacitor, it is possible to suppress a decrease in capacitance or a decrease in dielectric constant at high temperatures while ensuring excellent dielectric properties and circuit adhesion. That is, the dielectric layer containing the resin composition of the present invention has an inherently high electrostatic capacitance, and the high electrostatic capacitance is unlikely to decrease even at high temperatures. Nevertheless, the dielectric layer containing the resin composition of the present invention also has excellent circuit adhesion, and the circuit peeling in the capacitor is unlikely to occur.
[0018] The epoxy resin is not particularly limited as long as it has two or more epoxy groups in the molecule and can be used for electrical and electronic material applications. The preferred content of the epoxy resin in the resin composition is 15 to 80 parts by weight, more preferably 40 to 65 parts by weight, and even more preferably 45 to 60 parts by weight, relative to 100 parts by weight of the resin component. Examples of the epoxy resin include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, phenol novolac type epoxy resin, biphenyl novolac type epoxy resin, cresol novolac type epoxy resin, alicyclic epoxy resin, glycidylamine type epoxy resin, naphthalene type epoxy resin, anthracene type epoxy resin, dicyclopentadiene type epoxy resin, and any combination thereof. From the viewpoint of maintaining the heat resistance of the cured product, aromatic epoxy resin or polyfunctional epoxy resin is preferred, and more preferably phenol novolac type epoxy resin, naphthalene type epoxy resin, cresol novolac type epoxy resin, or biphenyl novolac type epoxy resin.
[0019] The diamine compound is not particularly limited as long as it functions as a curing agent for epoxy resin, has two amino groups in the molecule, and can be used for electrical and electronic materials. The preferred content of the diamine compound in the resin composition of the present invention is an amount in which the number of active hydrogen groups of the diamine compound is 0.5 to 1.5, more preferably an amount in which the number of active hydrogen groups of the diamine compound is 0.8 to 1.2, and even more preferably an amount in which the number of active hydrogen groups of the diamine compound is 0.9 to 1.1, when the number of epoxy groups of the epoxy resin is 1. Here, the "number of epoxy groups of the epoxy resin" is the value obtained by dividing the solid content mass of the epoxy resin present in the resin component by the epoxy equivalent. In addition, the "number of active hydrogen groups of the diamine compound" is the value obtained by dividing the solid content mass of the diamine compound present in the resin component by the active hydrogen group equivalent. Examples of the diamine compound include 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ether, 1,4- Examples thereof include bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis(aminomethyl)cyclohexane, and any combination thereof, and preferably 4,4'-diaminodiphenyl sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, and 2,2-bis[4-(4-aminophenoxy)phenyl]propane.
[0020] In addition, a curing accelerator can be added to the resin composition to accelerate the reaction of the resin. Preferable examples of the curing accelerator include imidazole-based and amine-based curing accelerators. From the viewpoint of storage stability and curing efficiency of the resin composition, the content of the curing accelerator is preferably 0.01 to 3 parts by weight, more preferably 0.1 to 2 parts by weight, based on 100 parts by weight of the non-volatile components in the resin composition.
[0021] The imidazole-based curing accelerator is incorporated into the molecular structure as part of the epoxy resin without being liberated as an ion after the curing reaction with the epoxy resin, and therefore can provide the resin layer with excellent dielectric properties and insulation reliability. The content of the imidazole-based curing accelerator is not particularly limited, and may be appropriately determined as an amount that provides desired curing while taking into account various conditions such as the composition of the resin layer. Examples of imidazole hardening accelerators include 2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 2-phenyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-methylimidazole, 1,2-dimethylimidazole, 2-phenylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole. Imidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and any combination thereof.Preferred examples of the imidazole-based hardening accelerator include 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenyl-4-methylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole. Among these, 2-phenyl-4-methylimidazole and 2-phenyl-4-methyl-5-hydroxymethylimidazole, which are imidazole-based hardening accelerators having a phenyl group, are more preferred from the viewpoint of chemical stability in the semi-cured (B stage) state of the resin layer. Among these, 2-phenyl-4-methyl-5-hydroxymethylimidazole is particularly preferred.
[0022] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, and any combination thereof.
[0023] The polyimide resin contributes to reducing the dielectric loss tangent. The content of the polyimide resin in the resin composition is preferably 10 parts by weight or more and 60 parts by weight or less, more preferably 20 parts by weight or more and 40 parts by weight or less, and even more preferably 30 parts by weight or more and 40 parts by weight or less, relative to 100 parts by weight of the resin component. With such a content, excellent dielectric properties can be exhibited while ensuring good heat resistance. The polyimide resin is not particularly limited as long as the desired dielectric properties, adhesion and heat resistance can be obtained, but a polyimide resin soluble in an organic solvent (hereinafter referred to as an organic solvent-soluble polyimide) is preferable from the viewpoint of forming a varnish and a coating film that are well compatible with the epoxy resin. The organic solvent in which the polyimide resin is soluble is preferably one having a solubility parameter (SP value) of 7.0 or more and 17.0 or less, and preferred examples of such organic solvents include methyl ethyl ketone, toluene, xylene, N-methylpyrrolidone, dimethylacetamide, dimethylformamide, cyclopentanone, cyclohexanone, cyclohexane, methylcyclohexane, ethylene glycol, ethylene glycol dimethyl ether, ethylene glycol acetate, and any combination thereof. In particular, those having at least one functional group capable of reacting with an epoxy group at the molecular end are preferred in terms of maintaining heat resistance after curing. Specifically, the polyimide resin preferably has at least one functional group selected from the group consisting of a carboxyl group, a sulfonic acid group, a thiol group, and a phenolic hydroxyl group as a functional group at its end or side chain. By having such a functional group, the heat resistance of the polyimide resin is maintained while the solubility in organic solvents and the compatibility with epoxy resins are improved. Among these, it is more preferred to use a polyimide resin having a carboxyl group as a functional group at its end or side chain.
[0024] A preferred organic solvent-soluble polyimide is one obtained by imidizing a tetracarboxylic dianhydride with a diamine compound. Examples of tetracarboxylic dianhydrides include 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenyl)phenyl]propane dianhydride, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzoxazole dianhydride, 2,2',3,3'-biphenyltetracarboxylic ... Examples of such anhydride include dibenzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 1,2,5,6-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 2,3,5,6-pyridine tetracarboxylic dianhydride, 3,4,9,10-perylene tetracarboxylic dianhydride, and the like, or compounds having alkyl or halogen atom substituents on these aromatic rings, and any combinations thereof. Among these, from the viewpoint of improving the heat resistance of the resin composition, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenyl)phenyl]propane dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, or a polyimide resin mainly composed of 2,2',3,3'-biphenyltetracarboxylic dianhydride is preferred. On the other hand, examples of the diamine compound include those mentioned above.
[0025] In particular, as the polyimide resin alone, a polyimide resin having a dielectric constant in the range of 2.0 or more and 5.0 or less and a dielectric tangent in the range of 0.0005 or more and 0.010 or less at a frequency of 1 GHz is preferably used in the resin composition of the present invention. More preferably, it is a polyimide resin having a dielectric constant in the range of 2.0 or more and 4.0 or less and a dielectric tangent in the range of 0.001 or more and 0.005 or less.
[0026] The dielectric filler is a component that provides a desired high capacitance to the resin composition as a dielectric layer, and is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta, and Bi. Preferred examples of the composite metal oxide include particles of BaTiO3, SrTiO3, Pb(Zr,Ti)O3, PbLaTiO3, PbLaZrO, SrBi2Ta2O9, and any combination thereof, which have a high capacitance and can be mixed into the resin composition of the present invention. More preferably, it is BaTiO3. Note that Pb(Zr,Ti)O3 means Pb(Zr x Ti 1-x )O3 (where 0 ≦ x ≦ 1, typically 0 < x < 1). The content of the dielectric filler in the resin composition is 60 parts by weight or more and 85 parts by weight or less, preferably 70 parts by weight or more and 85 parts by weight or less, more preferably 75 parts by weight or more and 85 parts by weight or less, based on 100 parts by weight of the solid content of the resin composition. Also, the particle size of the dielectric filler is not particularly limited, but from the viewpoint of maintaining the adhesion between the resin composition and the copper foil, the average particle size D 50 measured by laser diffraction scattering particle size distribution measurement is preferably 0.01 μm or more and 2.0 μm or less, more preferably 0.05 μm or more and 1.0 μm or less, and even more preferably 0.1 μm or more and 0.5 μm or less.
[0027] If desired, the resin composition may further contain a filler dispersant. By further containing a filler dispersant, the dispersibility of the dielectric filler can be improved when the resin varnish and the dielectric filler are kneaded. The filler dispersant may be any known dispersant that can be used appropriately, and is not particularly limited. Examples of preferred filler dispersants include ionic dispersants such as phosphonic acid type, cationic type, carboxylic acid type, and anionic type dispersants, as well as nonionic dispersants such as ether type, ester type, sorbitan ester type, diester type, monoglyceride type, ethylene oxide addition type, ethylenediamine base type, and phenol type dispersants. Other examples include coupling agents such as silane coupling agents, titanate coupling agents, and aluminate coupling agents.
[0028] Resin Coated Copper Foil The resin composition of the present invention is preferably used as a resin for a resin-coated copper foil. By forming the resin-coated copper foil in advance, it is possible to efficiently manufacture a capacitor element or a printed wiring board with a built-in capacitor without separately forming a resin layer or a dielectric layer. That is, according to a preferred embodiment of the present invention, a resin-coated copper foil is provided, which includes a copper foil and a resin composition provided on at least one side of the copper foil. Typically, the resin composition is in the form of a resin layer, and the resin composition is applied to the copper foil using a gravure coating method so that the thickness of the resin layer after drying is a predetermined value, and then dried to obtain a resin-coated copper foil. The coating method is arbitrary, but in addition to the gravure coating method, a die coating method, a knife coating method, etc. can be adopted. In addition, it is also possible to apply the coating using a doctor blade, a bar coater, etc. The resin composition in the resin-coated copper foil is preferably semi-cured from the viewpoint of forming a dielectric layer by laminating two resin-coated copper foils so that the resin compositions face each other.
[0029] The thickness of the resin layer is not particularly limited as long as the desired capacitance can be secured when the resin layer is incorporated into a capacitor as a dielectric layer, but is preferably 0.1 μm to 15 μm, more preferably 0.2 μm to 10 μm, particularly preferably 0.5 μm to 5 μm, and most preferably 1 μm to 3 μm. A thickness within these ranges has the advantages of easily achieving a high capacitance, easily forming a resin layer by applying a resin composition, and easily securing sufficient adhesion with the copper foil.
[0030] The copper foil may be a metal foil (so-called raw foil) that has been electrolytically or rolled, or may be in the form of a surface-treated foil that has been surface-treated on at least one side. The surface treatment may be any of various surface treatments that are performed to improve or impart certain properties (e.g., rust resistance, moisture resistance, chemical resistance, acid resistance, heat resistance, and adhesion to a substrate) to the surface of the metal foil. The surface treatment may be performed on at least one side of the metal foil, or on both sides of the metal foil. Examples of surface treatments performed on copper foil include rust prevention treatment, silane treatment, roughening treatment, and barrier formation treatment.
[0031] The ten-point average roughness Rzjis of the surface of the copper foil on the resin layer side, measured according to JIS B0601-2001, is preferably 2.0 μm or less, more preferably 1.5 μm or less, even more preferably 1.0 μm or less, and particularly preferably 0.5 μm or less. Within such a range, the thickness of the resin layer can be made thinner. The lower limit of the ten-point average roughness Rzjis of the surface of the copper foil on the resin layer side is not particularly limited, but from the viewpoint of improving the adhesion with the resin layer, Rzjis is preferably 0.005 μm or more, more preferably 0.01 μm or more, and even more preferably 0.05 μm or more.
[0032] The thickness of the copper foil is not particularly limited, but is preferably 0.1 μm or more and 100 μm or less, more preferably 0.5 μm or more and 70 μm or less, even more preferably 2 μm or more and 70 μm or less, particularly preferably 10 μm or more and 70 μm or less, and most preferably 10 μm or more and 35 μm or less. If the thickness is within these ranges, it is possible to adopt a method such as the MSAP (modified semi-additive) method, the SAP (semi-additive) method, or the subtractive method, which is a general pattern formation method for forming wiring on a printed wiring board. However, when the thickness of the copper foil is, for example, 10 μm or less, the resin-coated copper foil of the present invention may be a carrier-coated copper foil having a release layer and a carrier and a resin layer formed on the copper foil surface to improve handling.
[0033] Dielectric Layer The resin composition of the present invention is preferably cured to form a dielectric layer. That is, according to a preferred embodiment of the present invention, a dielectric layer is provided, which is a layer obtained by curing the resin composition of the present invention. The resin composition may be cured based on a known method, but is preferably cured by hot vacuum pressing. The thickness of the dielectric layer is not particularly limited as long as the desired capacitance can be secured, but is preferably 0.2 μm or more and 30 μm or less, more preferably 0.5 μm or more and 20 μm or less, particularly preferably 1 μm or more and 10 μm or less, and most preferably 2 μm or more and 6 μm or less. If the thickness is within these ranges, there are advantages such as easy realization of high capacitance, easy formation of a resin layer by application of the resin composition, and easy securing of sufficient adhesion with the copper foil.
[0034] Copper Clad Laminate The resin composition of the present invention or the dielectric layer containing the same is preferably applied to a copper-clad laminate. That is, according to a preferred embodiment of the present invention, a copper-clad laminate is provided which is provided with a first copper foil, the above-mentioned dielectric layer, and a second copper foil in this order. By forming the copper-clad laminate in the form of a copper-clad laminate, a capacitor element or a capacitor-embedded printed wiring board containing the resin composition of the present invention as a dielectric layer can be preferably produced. The method for producing the copper-clad laminate is not particularly limited, but for example, a copper-clad laminate can be produced by laminating two of the above-mentioned resin-coated copper foils so that the resin layers face each other and vacuum pressing at high temperature.
[0035] Capacitor element and capacitor-embedded printed wiring board The resin composition of the present invention or a dielectric layer containing the same is preferably incorporated into a capacitor element. That is, according to a preferred embodiment of the present invention, a capacitor element having the above-mentioned dielectric layer is provided. The configuration of the capacitor element is not particularly limited, and a known configuration can be adopted. A particularly preferred embodiment is a capacitor-embedded printed wiring board in which a capacitor or its dielectric layer is incorporated as an inner layer part of a printed wiring board. That is, according to a particularly preferred embodiment of the present invention, a capacitor-embedded printed wiring board having the above-mentioned dielectric layer is provided. In particular, by using the resin-coated copper foil of the present invention, a capacitor element or a capacitor-embedded printed wiring board can be efficiently manufactured based on a known method. EXAMPLES
[0036] The present invention will now be further illustrated by the following examples.
[0037] Examples 1-25 (1) Preparation of resin varnish First, the following resin component, imidazole-based curing accelerator, dielectric filler, and dispersant were prepared as raw material components for a resin varnish. - Epoxy resin: Biphenyl type epoxy resin, manufactured by Nippon Kayaku Co., Ltd., NC-3000H (biphenyl aralkyl type, epoxy equivalent 288g / Eq) - Diamine compound: Wakayama Seika Kogyo Co., Ltd., BAPP (2,2-bis[4-(4-aminophenoxy)phenyl]propane, active hydrogen group equivalent 102g / Eq) - Active ester resin: HPC-8000-65T (active ester equivalent: 223g / Eq), manufactured by DIC Corporation - Phenol resin: MEH-7500 (hydroxyl equivalent: 95g / Eq), manufactured by Meiwa Kasei Co., Ltd. - Aromatic polyamide resin: BPAM-155 (phenolic hydroxyl group-containing polybutadiene modified aromatic polyamide resin) manufactured by Nippon Kayaku Co., Ltd. - Polyimide resin: Arakawa Chemical Industries, Ltd., PIAD-301 (terminal functional group: carboxyl group, solvent: mixture of cyclohexanone, methylcyclohexane and ethylene glycol dimethyl ether, dielectric constant (1GHz): 2.70, dielectric tangent (1GHz): 0.003) - Butyral resin: KS-5Z, manufactured by Sekisui Chemical Co., Ltd. - Imidazole curing accelerator: Shikoku Chemical Industry Co., Ltd., 2P4MHZ, added amount 1.0wt% (based on 100wt% of resin component) - Dielectric filler: BaTiO3, manufactured by Nippon Chemical Industry Co., Ltd., AKBT-S, average particle size D measured by laser diffraction scattering particle size distribution measurement 50 =0.3μm - Dispersant: Titanate coupling agent, manufactured by Ajinomoto Fine-Techno Co., Ltd., KR-44
[0038] The raw material components for the resin varnish were weighed out in the mixing ratios (weight ratios) shown in Tables 1 to 3. Then, cyclopentanone solvent was weighed out, and the raw material components for the resin varnish and cyclopentanone were charged into a flask and stirred at 60° C. After confirming that the resin varnish was transparent, the resin varnish was collected.
[0039] (2) Mixing with filler Cyclopentanone solvent, dielectric filler, and dispersant were weighed. The weighed solvent, dielectric filler, and dispersant were slurried in a dispersing machine. After the slurry was confirmed, the resin varnish was weighed and kneaded with the dielectric filler-containing slurry in the dispersing machine to obtain a resin composition.
[0040] (3) Resin coating As shown in Fig. 1, the obtained resin composition 4 was applied to a copper foil 2 (manufactured by Mitsui Mining & Smelting Co., Ltd., thickness 18 μm, surface roughness Rzjis = 0.5 μm) using a bar coater so that the thickness of the resin layer after drying would be 1.5 μm, and then it was dried for 3 minutes in an oven heated to 160 ° C. to semi-cure the resin. In this way, a resin-coated copper foil 6 was obtained.
[0041] (4) Press As shown in FIG. 1, two sheets of resin-coated copper foil 6 were laminated with the resin compositions 4 facing each other, and then subjected to a pressure of 40 kgf / cm 2 Then, the laminate was vacuum pressed at 200° C. for 90 minutes to cure the resin composition 4. A copper-clad laminate 8 was obtained which contained the cured resin composition 4 as a dielectric layer and had a dielectric layer thickness of 3.0 μm.
[0042] (5) Circuit formation and evaluation One side of the obtained copper-clad laminate 8 was etched to form a circuit 10 for various evaluations, and the following various evaluations were carried out.
[0043] <Evaluation 1: Peel strength> One side of the copper-clad laminate 8 was etched to form a linear circuit 10 with a width of 10 mm, and the circuit 10 was then peeled off at a peeling speed of 50 mm / min using an autograph to measure the peel strength. This measurement was performed in accordance with IPC-TM-650 2.4.8. The measured peel strength was evaluated according to the following criteria. The results are shown in Tables 1 to 3. - Rating A: 0.6kgf / cm or more (good) - Rating B: 0.4kgf / cm or more and less than 0.6kgf / cm (acceptable) - Rating C: Less than 0.4kgf / cm (unacceptable)
[0044] <Evaluation 2: Capacitance measurement> One side of the copper-clad laminate 8 was etched to form a circular circuit 10 with a diameter of 0.5 inches (12.6 mm), and the capacitance was measured at a frequency of 1 kHz using an LCR meter (HIOKI EE Corporation, LCR HiTester 3532-50). This measurement was performed in accordance with IPC-TM-650 2.5.2. The results are shown in Tables 1 to 3. - Rating A: 40nF / in 2 Above (good) - Rating B: 20nF / in 2 or more and 40nF / in 2 Less than (OK) - Rating C: 20nF / in 2 Less than (not acceptable)
[0045] <Evaluation 3: Capacitance decrease rate after heat treatment> After the sample had been subjected to Evaluation 2, it was placed in an oven at 230°C for 110 minutes, and the capacitance was measured again to calculate the capacitance loss rate before and after the heat treatment. The same heat treatment was then repeated, and the capacitance loss rate after three heat treatments was calculated and evaluated according to the following criteria. The results are shown in Tables 1 to 3. - Rating A: Less than 2% (good) - Grade B: 2% or more and less than 5% (acceptable) - Rating C: 5% or more (unacceptable)
[0046] <Evaluation 4: Measurement of dielectric tangent> One side of the copper-clad laminate 8 was etched to form a circular circuit 10 with a diameter of 0.5 inches (12.6 mm), and the dielectric tangent at a frequency of 1 kHz was measured using an LCR meter (HIOKI EE Corporation, LCR HiTester 3532-50). This measurement was performed in accordance with IPC-TM-650 2.5.2. The results are shown in Tables 1 to 3. - Rating A: Less than 0.010 (good) - Rating B: 0.010 or more and less than 0.020 (acceptable) - Rating C: 0.020 or higher (unacceptable)
[0047] <Overall rating> The overall evaluation was determined by applying the evaluation results of 1 to 4 to the following criteria. The results are shown in Tables 1 to 3. - Rating A: All ratings are A (good) - Rating B: There are no items rated C, but there is at least one item rated B (passable) - Rating C: At least one C rating (not acceptable)
[0048] [Table 1]
[0049] [Table 2]
[0050] [Table 3]
Claims
1. A resin composition comprising: a resin component including an epoxy resin, a diamine compound, and a polyimide resin having a carboxyl group as a terminal functional group; A dielectric filler which is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta and Bi, in an amount of 70 parts by weight or more and 85 parts by weight or less relative to 100 parts by weight of the solid content of the resin composition; Including, The content of the polyimide resin is 10 parts by weight or more and 60 parts by weight or less with respect to 100 parts by weight of the resin component, The content of the epoxy resin is 15 parts by weight or more and 80 parts by weight or less relative to 100 parts by weight of the resin component, The resin composition has a content of the diamine compound such that, when the number of epoxy groups in the epoxy resin is taken as 1, the number of active hydrogen groups in the diamine compound is 0.5 or more and 1.5 or less.
2. The composite metal oxide is BaTiO 3 , SrTiO 3 , Pb(Zr,Ti)O 3 , PbLaTiO 3 , PbLaZrO, and SrBi 2 T 2 O 9 The resin composition according to claim 1, comprising at least one selected from the group consisting of:
3. The composite metal oxide is BaTiO 3 The resin composition according to claim 1 or 2,
4. The resin composition according to any one of claims 1 to 3, wherein the content of the diamine compound is an amount such that the number of active hydrogen groups of the diamine compound is 0.8 to 1.2 when the number of epoxy groups of the epoxy resin is 1.
5. The resin composition according to any one of claims 1 to 4, comprising 20 parts by weight or more and 40 parts by weight or less of the polyimide resin relative to 100 parts by weight of the resin component.
6. A resin-coated copper foil comprising a copper foil and the resin composition according to any one of claims 1 to 5 provided on at least one surface of the copper foil.
7. A dielectric layer, which is a layer obtained by curing the resin composition according to any one of claims 1 to 5.
8. The dielectric layer according to claim 7 , wherein the thickness of the dielectric layer is 0.2 μm or more and 30 μm or less.
9. The dielectric layer according to claim 8 , wherein the thickness of the dielectric layer is from 1 μm to 10 μm.
10. A copper-clad laminate comprising, in order, a first copper foil, the dielectric layer according to any one of claims 7 to 9, and a second copper foil.
11. A capacitor element comprising the dielectric layer according to any one of claims 7 to 9.
12. A printed wiring board with a built-in capacitor, comprising the dielectric layer according to any one of claims 7 to 9.
13. A method for producing a resin-coated copper foil, comprising: applying a resin composition to a copper foil, the resin composition comprising: a resin component including an epoxy resin, a diamine compound, and a polyimide resin having a carboxyl group as a terminal functional group; and a dielectric filler which is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta, and Bi, in an amount of 70 parts by weight or more and 85 parts by weight or less relative to 100 parts by weight of a solid content of the resin composition; wherein the content of the polyimide resin is 10 parts by weight or more and 60 parts by weight or less relative to 100 parts by weight of the resin component, the content of the epoxy resin is 15 parts by weight or more and 80 parts by weight or less relative to 100 parts by weight of the resin component, and the content of the diamine compound is such that, when the number of epoxy groups in the epoxy resin is defined as 1, the number of active hydrogen groups in the diamine compound is 0.5 to 1.5.
Citation Information
Patent Citations
Thermosetting resin composition and its use
JP2007231125A
Compositions comprising polyimides and hydrophobic epoxies, and methods therefor
JP2009511717A
Polymer-ceramic composite material with excellent TCC
JP2010539285A
Dielectric filler-containing resin for forming built-in capacitor layer of printed wiring board, double-sided copper-clad laminate with dielectric layer formed using the dielectric-filler-containing resin, and method for producing double-sided copper-clad laminate
JP4148501B2
Copper foil with dielectric layer
WO2009008471A1